Diagnosis of calcium pyrophosphate dihydrate crystal deposition disease: ultrasonographic criteria proposed. Issue 4 (15th March 2005) - Frediani, B; Filippou, G; Falsetti, P; Lorenzini, S; Baldi, F; Acciai, C; Siagkri, C; Marotto, D; Galeazzi, M; Marcolongo, R
Abstract : Objective: To investigate by high frequency ultrasonography the appearance of calcium pyrophosphate dihydrate (CPPD) calcifications, in the most commonly affected sites in CPPD disease, and the relationship between ultrasonographic CPPD deposits and the presence of CPPD crystals in synovial fluid. Methods: Three ultrasonographic patterns of CPPD calcification were identified and 11 patients enrolled. A control group comprised 13 patients with no evidence of CPPD deposits. Synovial fluid was aspirated from all patients and controls and examined for identification of crystals. All patients underwent a standard radiography examination at the same sites investigated by ultrasound. Results: In all patients with ultrasonographically defined CPPD deposits, CPPD crystals were found in the synovial fluid. In two cases, standard radiographic examination did not show evidence of the calcific deposits that were identified by ultrasonography. CPPD crystals were not found in the synovial fluid of controls. In four control group patients, ultrasonography identified calcifications defined as deposits of another nature. Conclusions: The ultrasonographic pattern used in this study for the diagnosis of CPPD disease demonstrated a very high correlation with the presence of CPPD crystals in synovial fluid. Ultrasonography demonstrated a sensitivity and specificity at least equal to that of radiography in identifying CPPD crystal calcifications.